Application of a split‐Cre system for high‐capacity adenoviral vector amplification. Issue 3 (12th December 2022) - Gonzalez‐Aparicio, Manuela; Bunuales, Maria; de Landazuri, Iñaki Ortiz; Prieto, Jesus; Hernandez‐Alcoceba, Ruben
Abstract: Background and Aims: High‐capacity adenoviral vectors (HC‐AdV) show extended DNA payload and stability of gene expression in vivo due to the absence of viral coding sequences. However, production requires methods to trans‐complement viral proteins, usually through Helper Viruses (HV). The Cre/loxP system is frequently employed to remove the packaging signal in HV genomes, in order to avoid their encapsidation. However, chronic exposure to the Cre recombinase in packaging cells is detrimental. We have applied the dimerizable Cre system to overcome this limitation. Methods and Results: Cre was split in two fragments devoid of recombinase function (N‐terminal 244 and C‐terminal 99 amino‐acids). In one version of the system, interaction with both moieties was favored by rapamycin‐dependent heterodimerization domains (DiCre). Other version contained only Cre sequences (oCre). We generated packaging cells and HVs expressing the complementary fragments and studied their performance for HC‐AdV production. We found that both conformations avoided interference with the growth of packaging cells, and the oCre system was particularly suitable for HC‐AdV amplification. Conclusions: The split‐Cre system improves the performance of packaging cells and can reduce the time and cost of HC‐AdV amplification up to 30% and 15%, respectively. This may contribute to the standardization of HC‐AdV production. Graphical Abstract and Lay Summary: Production of high‐capacity adenoviral vectors requires co‐infection with helper viruses. The Cre‐loxP system is frequently used to cleave the packaging signal (Ψ) of the helper virus in order to avoid encapsidation. However, packaging cells constitutively expressing the recombinase show impaired proliferation. To solve this problem, the authors have split the Cre recombinase in two inactive segments. One of them is expressed by the cells, and the other one by the helper virus. The recombinase function is only restored when the cells are infected by the helper virus during the process of vector production. Using this strategy, amplification of packaging cells is enhanced and the efficiency of the protocol is increased. This improvement can facilitate the large‐scale production of vectors for clinical use.